Risk management of neurobehavioral health of tyre manufacturing industry workers exposed to naphtha - Norazura, Ismail (2011)
Introduction: Neurobehavioral effects on cognitive functioning and motor disturbances were linked to organic solvents even in setting exposure standards in the workplace which may interfere with job tasks resulting in costly injuries and lost of productivity. This study is aimed to assess and manage the risks of naphtha exposure and the neurobehavioral health effects among workers in a tyre manufacturing industry. Methodology: A cross-sectional study was carried out in Phase I, followed by an intervention study in Phase II. A total of 119 male workers exposed to naphtha were universally recruited as the exposed group, while 72 male administrative workers who did not exposed to naphtha were selected as the unexposed group. In Phase I, questionnaires were used to collect the information on general background, occupational profile and the risk factors. Environmental and personal air monitoring were carried out using a portable volatile organic compound (VOC) monitor and personal air sampling pump. Neurobehavioral performance was measured using the Neurobehavioral Core Test Battery (NCTB).